FEASIBILITY OF PALIPERIDONE FOR TRANSDERMAL THERAPEUTIC SYSTEMS: EX VIVO PERMEATION KINETIC STUDIES OF DRUG THROUGH RAT ABDOMINAL SKIN - SADASHIVAIAH R; ROHITH G; SATHEESHA BABU BK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of the current research study was to investigate the effect of various permeation enhancers on the skin permeation of paliperidone for transdermal therapeutic systems (TTS). Methods: A part of pre-formulation studies was performed to authentication of the drug by determining the melting point, solubility, partition coefficient (PC), attenuated total reflection-Fourier transform infrared, differential scanning calorimetry, and its purity by reversed-phase high-performance liquid chromatography. Ex vivo permeation kinetic study for paliperidone alone and with 5% concentration of permeation enhancers hyaluronidase, dimethylsulfoxide (DMSO), groundnut oil, and tween 80 was conducted in modified Franz diffusion cell through rat abdominal skin as a barrier. The receptor phase containing 20% polyethylene glycol 400 in normal saline was maintained at 37°C. The steady-state flux was obtained to calculate permeability coefficient, enhancement ratio (ER), and the cumulative amount of drug permeated at 12 h. Results: The pre-formulation study results indicated that the received pure drug was authentified as paliperidone and its purity at par with official pharmacopeia. The PC of the drug was found to be 1.916±1.07, indicated that the drug to be lipophilic. The ex vivo permeation study results showed that the enhancement effect of some permeation enhancers on paliperidone was as follows: Hyaluronidase>DMSO>groundnut oil>tween 80. Hyaluronidase has high permeation enhancing activity with the highest permeation flux of 12.038 μg/cm2/h, and the cumulative amount of drug permeated was 212.760 μg/cm2. The ER of hyaluronidase was 3.69 folds higher than control. Conclusion: The results of the present research study attributed that hyaluronidase was a potential permeation enhancer which would be included in the TTS of paliperidone.